Khropr̨̄op 90 pī Krasūang Khamanākhom (K̨̄ong Klāng, Samnakngān Palat Krasūang Khamanākhom, 2002)
Commemorative volume brought out on occasion of 90th anniversary of Ministry of Transport and Communications; comprises its organizational structure, history and development, and functions.